Maternal Obesity, Maternal Overnutrition and Fetal Programming: Effects of Epigenetic Mechanisms on the Development of Metabolic Disorders - Şanlı, Ezgi; Kabaran, Seray (Current genomics, 2019)
Background: Maternal obesity and maternal overnutrition, can lead to epigenetic alterations during pregnancy and these alterations can influence fetal and neonatal phenotype which increase the risk of metabolic disorders in later stages of life. Objective: The effects of maternal obesity on fetal programming and potential mechanisms of maternal epigenetic regulation of gene expression which have persistent effects on fetal health and development were investigated. Methods: Review of the literature was carried out in order to discuss the effects of maternal obesity and epigenetic mechanisms in fetal programming of metabolic disorders. All abstracts and full-text articles were examined and the most relevant articles were included in this review. Results: Maternal obesity and maternal overnutrition during fetal period has important overall effects on long-term health. Maternal metabolic alterations during early stages of fetal development can lead to permanent changes in organ structures, cell numbers and metabolism. Epigenetic modifications (DNA methylation, histone modifications, microRNAs) play an important role in disease susceptibility in the later stages of human life. Maternal nutrition alter expression of hypothalamic genes which can increase fetal and neonatal energy intake. Epigenetic modifications may affect the increasing rate of obesity and other metabolic disorders worldwide since the impact of these changes can be passed through generations. Conclusion: Weight management before and during pregnancy, together with healthy nutritional intakes may improve the maternal metabolic environment, which can reduce the risks of fetal programming of metabolic diseases. Further evidence from long-term follow-up studies are needed in order to determine the role of maternal obesity on epigenetic mechanisms.